O Projeto Professor Diretor de Turma como política pública educacional: impactos no contexto da Escola de Ensino Médio Luiza Bezerra de Farias em Tururu - Barros, Romão Francisco de Oliveira (Universidade do Vale do Rio dos Sinos, 2021)
This research analyzed the Project Teacher Director of the Class (PPDT), its performance and its impacts on the Luiza Bezerra de Farias High School (EEM), in the municipality of Tururu/ CE. The PPDT is a public policy, designed to reduce the negative levels of education in state schools in Ceará. It seeks not only to guarantee the permanence of the student in the classroom, but also to make them perceive themselves as subjects of their own learning and, therefore, better manage their teaching time. For this research, the analysis of changes in the role of the State, after the reforms of the 1990s, the diffusion of managerialism and entrepreneurship in the management of processes and the focus on performance and results, through ranking, was fundamental for establishing the historical context of this public policy. The time frame chosen for this investigation (2017 – 2019) aimed to analyze the pedagogical path of students, from their arrival in the first grade of High School, in 2017, to the conclusion of the third grade, in 2019. research with a qualitative approach that is empirically based on the analysis of documentation related to the project as well as data produced through structured questionnaires answered, in the virtual technological environment, by the classroom teachers and students, in addition to an interview with the coordinator of the project at school. As a result, it was observed that this public policy needs adjustments and corrections of routes throughout its performance processes linked to school actors, especially with regard to active listening to those involved in the management processes and in the continuing education of teachers Class Directors and better adaptation of the project to different school contexts. But, it was also found that the PPDT produces positive effects, especially linked to attendance and the reduction of dropouts and school dropouts; the mediation of conflicts, benefiting not only the insertion of students in the school environment, but also in the family and community; as well as the expansion of expectations for the continuity of studies in higher education.
Keywords: Política pública educacional; Desempenho escolar; Projeto Professor Diretor de Turma; Escola de Ensino Médio (EEM) Luiza Bezerra de Farias; Educational public policy; School performance; Class Director Teacher Project; High School (EEM) Luiza Bezerra de Farias; ACCNPQ::Ciências Humanas::Educação